Lumping kinetics of ABE fermentation wastewater treatment by oleaginous yeast Trichosporon cutaneum. Issue 9 (21st October 2017) - Wang, Can; Huang, Chao; Chen, Xue-Fang; Zhang, Hai-Rong; Xiong, Lian; Li, Xiao-Mei; Guo, Hai-Jun; Qi, Gao-Xiang; Lin, Xiao-Qing; Chen, Xin-De
ABSTRACT: Lumping kinetics models were built for the biological treatment of acetone–butanol–ethanol (ABE) fermentation wastewater by oleaginous yeast Trichosporon cutaneum with different fermentation temperatures. Compared with high temperature (33°C, 306 K) and low temperature (23°C, 296 K), medium temperature (28°C, 301 K) was beneficial for the cell growth and chemical oxygen demand (COD) degradation during the early stage of fermentation but the final yeast biomass and COD removal were influenced little. By lumping method, the materials in the bioconversion network were divided into five lumps (COD, lipid, polysaccharide, other intracellular products, other extracellular products), and the nine rate constants ( k 1 – k 9 ) for the models can well explain the bioconversion laws. The Gibbs free energy ( G ) for this bioconversion was positive, showing that it cannot happen spontaneous, but the existence of yeast can after the chemical equilibrium and make the bioconversion to be possible. Overall, the possibility of using lumping kinetics for elucidating the laws of materials conversion in the biological treatment of ABE fermentation wastewater by T. cutaneum has been initially proved and this method has great potential for further application.